1991
DOI: 10.1002/app.1991.070430708
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of olefins through heterogeneous catalysis. IX. Experimental study of propylene polymerization over a high activity MgCl2‐supported Ti catalyst

Abstract: SYNOPSISResults from an experimental study of propylene polymerization in heptane diluent over a high activity Mg-supported Ti catalyst are presented. The study provides an examination of the effect of operating conditions on polymerization rate, product melt index, and powder bulk density. Among the findings are that product bulk density decreases with increasing operating temperature and decreasing operating pressure while prepolymerization increases the bulk density. The results support the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…They are applied to bulk, slurry and gas‐phase propylene polymerization processes, where the kinetic behaviour and morphological development of olefin polymerization are most important issues. In general, the kinetic behaviour of polymerization with a moderate initial activity followed by a slow decay rate of the catalyst activity is practically efficient for producing desirable particle morphology and also to control reactor performance and conditions in the polymerization process 1–8. In addition, the morphology of powder particles, which is related to the morphology of catalyst particles through replica phenomena, strongly affects the productivity of polyolefin processes as well as excellent handling and processing properties of final polymer powders 1–8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are applied to bulk, slurry and gas‐phase propylene polymerization processes, where the kinetic behaviour and morphological development of olefin polymerization are most important issues. In general, the kinetic behaviour of polymerization with a moderate initial activity followed by a slow decay rate of the catalyst activity is practically efficient for producing desirable particle morphology and also to control reactor performance and conditions in the polymerization process 1–8. In addition, the morphology of powder particles, which is related to the morphology of catalyst particles through replica phenomena, strongly affects the productivity of polyolefin processes as well as excellent handling and processing properties of final polymer powders 1–8.…”
Section: Introductionmentioning
confidence: 99%
“…Floyd et al 9 and Hutchinson and Ray5 mentioned the necessity of controlling the initial growth of polymer particles using a prepolymerization step at low temperature and pressure for the development of good polymer particle morphology. They developed the comprehensive multigrain model (MGM) based on experimental observations, which is commonly used to explain the fragmentation and replication phenomena for ZN olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the so-called ''replication phenomenon'', whereby the size distribution of the catalyst particles is neatly replicated by the size distribution of the polymer particles exiting the reactor, as illustrated in [46][47][48][49][50]. This picture of particle fragmentation and growth has been captured in its most important details by the multigrain model [36,[51][52][53][54][55][56][57][58][59][60] which was originally developed to describe the crystalline structures of TiCl 3 and TiCl 4 /MgCl 2 Ziegler-Natta catalysts, but has also been used extensively to describe metallocene and late transition metals catalysts supported on inorganic carriers. In the multigrain model, the polymer particle is divided into two levels of mass-transfer resistances: the microparticles or primary particles, and the macroparticle or secondary particle.…”
Section: Single Particle Models -Mass-and Heat-transfer Resistancesmentioning
confidence: 99%
“…These equations are summarized in Table 8.2. Mathematical models for solving this system of partial differential equations with moving boundaries are involved and have been discussed in the literature [36,[51][52][53][54][55][56][57][58][59][60].…”
Section: Primary Particle or Microparticlementioning
confidence: 99%
“…The influence of prepolymerization on polymer particle morphology has also been the subject of investigation. Floyd et al and Hutchinson and Ray argued that to make polymer particles with good morphology, it was necessary to control the initial growth of the polymer particles in a prepolymerization stage at mild conditions. Pater et al showed that short prepolymerizations were adequate to make polymer particle with regular shapes.…”
Section: Introductionmentioning
confidence: 99%